Women Professor’s Ways of Working in Academia - Rachel Wlodarsky; Catherine Hansman (Adult Education Research Conference, 2019)
We address women’s development theories that might explain women professors’ academic identity, unique pressures faced by women faculty members, and how these issues impact work-life balance.
Keywords: Faculty Members Women’s Identity Career Stages Ethic of Care Mentoring